2021
DOI: 10.1371/journal.pone.0248336
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of COVID-19 incidence and outcomes: A rapid review

Abstract: Early reports indicate that the social determinants of health are implicated in COVID-19 incidence and outcomes. To inform the ongoing response to the pandemic, we conducted a rapid review of peer-reviewed studies to examine the social determinants of COVID-19. We searched Ovid MEDLINE, Embase, PsycINFO, CINAHL and Cochrane Central Register of Controlled Trials from December 1, 2019 to April 27, 2020. We also searched the bibliographies of included studies, COVID-19 evidence repositories and living evidence ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 82 publications
5
114
0
2
Order By: Relevance
“…11 In the COVID-19 pandemic, studies from most developed countries have reported greater COVID-19 related mortality and adverse outcomes among the ethnic minorities. 3,4,5 However, association of mortality among low socioeconomic or less educational status individuals are inconclusive. 3,4,12,13,14 In England, OpenSAFELY platform evaluated ethnic differences in COVID-19 related hospitalization, intensive care unit admission and death in 17 million adults from the National Health Service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 In the COVID-19 pandemic, studies from most developed countries have reported greater COVID-19 related mortality and adverse outcomes among the ethnic minorities. 3,4,5 However, association of mortality among low socioeconomic or less educational status individuals are inconclusive. 3,4,12,13,14 In England, OpenSAFELY platform evaluated ethnic differences in COVID-19 related hospitalization, intensive care unit admission and death in 17 million adults from the National Health Service.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,5 However, association of mortality among low socioeconomic or less educational status individuals are inconclusive. 3,4,12,13,14 In England, OpenSAFELY platform evaluated ethnic differences in COVID-19 related hospitalization, intensive care unit admission and death in 17 million adults from the National Health Service. 23 As compared to British White group, deaths were higher in South Asians in the first wave (OR 1.08, CI 1.07-1.09), and the second wave of COVID-19 epidemic (OR 1.87, CI 1.68-2.07) as well as in the overall cohort (OR 1.26, CI 1.15-1.37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, data examining the role of the social determinants of health within the context of the COVID-19 pandemic have been less prominent than research focusing on the biomedical paradigm [16,17]. A recent rapid review of COVID-19 studies examining infection, health service use, and health outcomes, found a minority of studies that had assessed outcomes according to social determinants of health [18]. Moreover, social determinants are rarely incorporated into mathematical modelling studies, which have achieved substantive importance in informing policy-makers about the impact of disease and interventions in the population over time [19,20].…”
Section: Introductionmentioning
confidence: 99%